Three Hurdles to Technology Integration: A Case Study of Technology Integration in Bungamati - Lee, Jeffrey Chih-Yih; Sparks, Paul (Journal of NELTA, 2014)
Integrating technology in education is an extraordinary challenge in rural villages of developing countries like Nepal. Since greater understandings of the circumstances surrounding teachers and schools could illuminate issues and opportunities for positive change, a case study of the telecenter in Bungamati, Nepal was conducted. Data, in the form of interviews, observations and related documents, were gathered and analyzed to highlight and understand the local hurdles for integrating technology in teaching. Findings were threefold: teachers lack technology integration skills; informal learning was the preferred way to learn technology; and males had greater access to technology. In this study, the researcher has drawn the following conclusions: a) teachers need technology access and training, b) administrators need a framework for integration, c) informal learning should be considered and promoted and d) there is a clear need for gender equity. Furthermore, suggestions for future studies include a need for informal learning, the use of the TPACK (Technological, Pedagogical, and Content Knowledge)framework for integration technology and more research in the area of teacher training with technology in other developing countries. DOI: http://dx.doi.org/10.3126/nelta.v18i1-2.10334 Journal of NELTA, Vol 18 No. 1-2, December 2013; 105-114